Extracting kinetic parameters of aniline polymerization from thermal data of a batch reactor. simulation of the thermal behavior of a reactor - Cavallo, Pablo César (2014)
A simulation model of the thermal behavior of a reactor during aniline polymerization is proposed. The model takes into account the polymerization mechanism together with heat production and dissipation. The temperature–time profiles can be simulated with different kinetic parameters. The model is used for two purposes: to extract kinetic parameters by fitting experimental temperature–time profiles of a cooled agitated batch reactor; and to estimate the temperatures changes occurring in a reactor under different experimental conditions to find the best conditions for industrial production of polyaniline. The rate equation used includes two rate constants: one in the absence of polymer (k1) and another in the presence of polymer (k2). The thermal factors, such as the heat transfer coefficient and the reaction enthalpy, are experimentally measured. A computer program is written that fits the experimental data using different kinetic parameters. The data analysis shows a temperature peak (Tmax) whose magnitude decreases when k2 decreases, whereas it is not affected by k1. The time to reach the Tmax is inversely proportional to k1 and k2. The model allows obtaining the kinetic parameters in different reaction media, e.g. varying the concentration of acid. The model is used to simulate the thermal behavior, to polymerize 1M of aniline: in one step the temperature of the reactor will increase till 82ºC, such thermal runaway will cause polymer degradation, successive additions of portions of the total oxidant amount, paced at defined time intervals, is devised to maintain low temperatures while producing the same amount of polymer.